ASSOCIATION BETWEEN HbA1c WITH PLATELET TO LYMPHOCYTE RATIO AND NEUTROPHIL TO LYMPHOCYTE RATIO IN TYPE 2 DIABETES MELLITUS - Villarsi, Devinda; Brama Ihsan Sazli; Pase, M Aron (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease in which inflammation plays a significant role in both microvascular and macrovascular complications. The Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) are simple hematological biomarkers that can reflect systemic inflammatory status and potentially correlate with HbA1c levels as an indicator of glycemic control. Objective: To determine the association between HbA1c levels and NLR and PLR in T2DM patients at Haji Adam Malik General Hospital, Medan. Methods: This was a retrospective cross-sectional study using secondary data from the medical records of T2DM patients between May and July 2024. A total of 96 patients met the inclusion criteria. Data were analyzed using the Kruskal-Wallis test with a significance level of p<0.05. Results: The median HbA1c of the patients was 9% (range 4.2–15.4%). Median NLR increased according to HbA1c categories: 3.91 (HbA1c <7%), 5.77 (HbA1c 7–9%), and 7.19 (HbA1c >9%) with p=0.012. Median PLR also increased across categories: 134.75, 189.00, and 233.33 with p=0.009. Conclusion: A significant association was observed between HbA1c and both NLR (p = 0.012) and PLR (p = 0.009). NLR and PLR can be used as additional hematological parameters to assess inflammation and glycemic control in patients with type 2 diabetes.